2019
DOI: 10.3389/fpsyt.2019.00828
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Level Predictors of Psychiatric Readmission in Substance Use Disorders

Abstract: Repeated psychiatric readmissions are a particular challenge in the treatment of substance use disorders and are associated with substantial burden for patients and their associates and for healthcare providers. Factors affecting readmission rates are heterogeneous and need to be identified to better allocate resources. Within the Swiss healthcare system, such data on substance use disorder patients are largely missing. Understanding these factors might bear important implications for future healthcare plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 39 publications
5
33
1
Order By: Relevance
“…Furthermore, higher rates of readmission in individuals who started using drugs in their youth, compared to people who started later in their life, were estimated [ 24 ]. Our findings confirm that comorbid substance use disorders may lead to symptomatic relapse, impair clinical and psychosocial adjustment, reduce medication adherence, and lower the response to treatment among subjects with severe mental disorders [ 25 , 26 ]. As for suicidality, our analysis estimated that individuals who were admitted because of a suicide attempt were more likely to be rehospitalized, consistently with previous studies showing an association between suicidal behavior and readmission in both adolescents [ 9 , 12 ] and adults with early psychosis [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, higher rates of readmission in individuals who started using drugs in their youth, compared to people who started later in their life, were estimated [ 24 ]. Our findings confirm that comorbid substance use disorders may lead to symptomatic relapse, impair clinical and psychosocial adjustment, reduce medication adherence, and lower the response to treatment among subjects with severe mental disorders [ 25 , 26 ]. As for suicidality, our analysis estimated that individuals who were admitted because of a suicide attempt were more likely to be rehospitalized, consistently with previous studies showing an association between suicidal behavior and readmission in both adolescents [ 9 , 12 ] and adults with early psychosis [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…However, readmissions are a common problem, 1,8,9 which underlines the importance of understanding risk factors of frequent hospital use among patients with SUD. In most cases patients with SUD can be treated adequately in outpatient programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study including mainly patients with multiple SUDs found that the substance used did not influence readmissions. 9 The individual HoNOS items which may have allowed a more in-depth analysis of predictive factors were not considered in this analysis. Future studies could control for this.…”
Section: Study Limitationsmentioning
confidence: 99%
“…For state hospital inpatients, the median length of stay was 34 days, whereas for patients hospitalized at other inpatient facilities, the median length of stay was only 7 days. Several prior studies have found that longer lengths of stay, or related measures such as adequate symptom resolution before discharge, are associated with a lower risk of readmission [e.g., 5,6,13,14]. Patients in other inpatient facilities may have been more likely to be readmitted because they received inadequate treatment while hospitalized.…”
Section: Discussionmentioning
confidence: 99%